2011
DOI: 10.3171/2010.12.spine10480
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal CCR1, CCL3(MIP-1α), CXCR4, CXCL12(SDF-1α) expression patterns in a rat spinal cord injury model of posttraumatic neuropathic pain

Abstract: Object Central neuropathic pain is a frequent challenging complication after spinal cord injury (SCI), and specific therapeutic approaches remain elusive. The purpose of the present investigations was to identify potential key mediators of these pain syndromes by analyzing detailed expression profiles of important chemokines in an experimental SCI paradigm of posttraumatic neuropathic pain in rats. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 44 publications
7
49
0
Order By: Relevance
“…The enhanced presence of CCL3 can also explain the immediate analgesic effects, independent from an anti-inflammatory action, evoked by the administration of the CCR1 antagonist J113863 in carrageenan-and CFA-inflamed mice. These results add new insights to the previously reported information related to the involvement of CCR1 in neuropathic [7,11,12,35] or neoplastic [10] pain. The possibility of inhibiting inflammatory pain following the acute administration of a CCR1 antagonist seems particularly interesting considering that CCR1 antagonists are already being tested in clinical trials, and that a CCR1 antagonist has been shown to improve rheumatoid arthritis without inducing remarkable adverse reactions [21].…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…The enhanced presence of CCL3 can also explain the immediate analgesic effects, independent from an anti-inflammatory action, evoked by the administration of the CCR1 antagonist J113863 in carrageenan-and CFA-inflamed mice. These results add new insights to the previously reported information related to the involvement of CCR1 in neuropathic [7,11,12,35] or neoplastic [10] pain. The possibility of inhibiting inflammatory pain following the acute administration of a CCR1 antagonist seems particularly interesting considering that CCR1 antagonists are already being tested in clinical trials, and that a CCR1 antagonist has been shown to improve rheumatoid arthritis without inducing remarkable adverse reactions [21].…”
Section: Discussionsupporting
confidence: 59%
“…The stimulation of CCR1 expressed in nociceptors causes Ca 2+ influx and enhances capsaicin responsiveness [6], and the local administration of CCR1 agonists elicits nociceptive behaviours in mice [9,10]. CCR1 is up-regulated in sensory neurons [11] and the spinal cord [7,12] after nerve injury and increased CCR1 mRNA has also been measured in rats 24 hr after receiving carrageenan [13], supporting its involvement in nociceptive processing. Functionally, it has been reported that some types of neuropathic pain can be alleviated by blocking CCR1 expression with siRNA [11], and that the administration of a CCR1 antagonist can prevent some types of murine bone cancer pain [10] and partially reduce writhing responses in mice receiving intraperitoneal acetic acid or mechanical hyperalgesia in inflamed mice [14].…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…A recent study showed that CXCL12 and its cognate receptor CXCR4 are constitutively expressed in the DRG and spinal cord of naïve rats [15,33]. In the DRG, CXCL12 and CXCR4 are widely distributed in small amounts in small-and medium-sized neurons and glial cells (satellite cells).…”
Section: Sni Upregulates Cxcl12 and Its Cognate Receptor Cxcr4 In Thementioning
confidence: 99%